2020
DOI: 10.3389/fbioe.2020.553270
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Visual Feedback Combining Vibrotactile Stimulation Promotes Embodiment Perception: An Electroencephalogram (EEG) Pilot Study

Abstract: As one determinant of the efficacy of mirror visual feedback (MVF) in neurorehabilitation, the embodiment perception needs to be sustainable and enhanced. This study explored integrating vibrotactile stimulation into MVF to promote the embodiment perception and provide evidence of the potential mechanism of MVF. In the experiment, the participants were instructed to keep their dominant hand still (static side), while open and close their non-dominant hand (active side) and concentrate on the image of the hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 58 publications
3
19
0
Order By: Relevance
“…The combination of these two strategies could lead to a synergistic gain effect. Previous studies showed that MVF induced the patient's embodiment of the feedback limb images through mirror illusion (Ding et al, 2020). Combined visual and proprioception feedback could enhance the perception of embodiment (Wittkopf et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…The combination of these two strategies could lead to a synergistic gain effect. Previous studies showed that MVF induced the patient's embodiment of the feedback limb images through mirror illusion (Ding et al, 2020). Combined visual and proprioception feedback could enhance the perception of embodiment (Wittkopf et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…As a new kind of mirror therapy, virtual reality mirror therapy (VRMT) can provide immersion mirror therapy for stroke patients [14]. However, mirror therapy lacks the participation of proprioception [15], which may not be able to simulate the actual scene well and activate the motor-related brain network to the greatest extent. As a clinical peripheral intervention technology, a large number of studies have proved that robot-assisted therapy (RAT) can have a positive impact on the recovery of upper limb motor dysfunction in stroke patients through programmed task training [16,17], including motor function and proprioception.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of ERD patterns in SES training block could be explained by the fact that the kinesthesia illusion evoked by st-SES strengthened proprioceptive afference related to MI tasks [34]. Recent evidence has shown that proprioceptive afference may play an important role in the formation of body representation and the improvement of neural activation [21].…”
Section: A Enhancement Of Neural Activationmentioning
confidence: 97%